Strength stabilization of peat soil using ordinary portland cement (OPC) - Marlene Insin, Jack (2016)
This article describes a laboratory study on stabilizing peat soil using Ordinary Portland Cement (OPC) to improve its strength. Peat soil commonly occur as extremely soft, wet, unconsolidated surficial deposits that are the major parts of the wetland systems. These problematic soils are well known for its high compressibility and low in shear strength. Therefore this soil were stabilized in order to solve the major problem that always encountered by the civil engineer in Malaysia. Various percentages of OPC which is 4, 6, and 8% were added to peat soil at optimum moisture content and the sample was cured for 7, 14 and 28 days before conducting Unconfined Compressive Strength test. The Unconfined Compressive Strength test show that the strength of the peat soil will increase as the percentage of the stabilizer increases.